The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/adfm.202205923
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficiency of Gallium Telluride for Photocatalysis, Electrocatalysis, and Chemical Sensing through Defects Engineering and Interfacing with its Native Oxide

Abstract: Gallium telluride (GaTe) is a van der Waals semiconductor, currently adopted for photonic and optoelectronic devices. However, the rapid degradation of GaTe in air, promoted by Te vacancies, is detrimental for device applications. Here, it is demonstrate that the surface oxidation of GaTe can be unexpectedly exploited for expanding the breadth of applications of GaTe. Specifically, the formation of a nanoscale sub-stoichiometric wide-band-gap Ga 2 O 3 skin, promoted by Te vacancies, over narrow-band-gap GaTe x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…Notably, at optimized higher temperatures, GaTe maintains its preferred monoclinic structure, although GaTe exhibits poor environmental stability. 44,45 Even then we could not see the additional peak of any oxide or other phases of GaTe such as Ga 2 O 3 or TeO 2 or Ga 2 Te 3 . 32,45,46 So, the absence of additional diffraction peaks from impurities serves as strong evidence of the high purity of the samples.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…Notably, at optimized higher temperatures, GaTe maintains its preferred monoclinic structure, although GaTe exhibits poor environmental stability. 44,45 Even then we could not see the additional peak of any oxide or other phases of GaTe such as Ga 2 O 3 or TeO 2 or Ga 2 Te 3 . 32,45,46 So, the absence of additional diffraction peaks from impurities serves as strong evidence of the high purity of the samples.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…Currently, 2D GaTe has two crystal structures: m-GaTe and h-GaTe, as shown in Figure a,b, respectively. The layer configuration of GaTe consists of a quadruple layer containing four atomic layers of Te–Ga–Ga–Te. , For h-GaTe, the Ga–Ga bonds are completely perpendicular to the layer plane with an atomic stacking sequence of ABBA, forming a hexagonal crystal structure . On the other hand, m-GaTe presents a twisted posture, with one-third of the Ga–Ga bond in the structure changing from an out-of-plane position to an in-plane position .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been found that introducing QDs to the surface of 2D nanomaterials increases the number of activation sites in 2D materials. As a result, most of the researchers are trying to make ultrasensitive detectors by using such heterojunctions. , There are several articles based on innovative 2D semiconductors, and their heterostructure sensor has been reported in the last few years. The research may have used a specific research design or methodology that has limitations. For example, the research may have relied on self-report measures, which could be subject to biases or may not fully capture the complexity of the phenomenon under investigation.…”
Section: Introductionmentioning
confidence: 99%